Karakterisasi Respons Elektrikal-Termal Transien LED COB pada Modul Aluminium Berbasis CNC terhadap Variasi Arus - Muhammad Rasyid Putera Agung; Ida Nurcahyani (Lembaga Pengembangan Kinerja Dosen, 2026)
Chip-on-board (COB) LEDs in high-power lighting systems require thermal characterization because temperature rise can affect forward voltage, electrical power, optical stability, and system reliability. This study aims to characterize the transient electrical-thermal response of a COB LED mounted on a CNC-based aluminum module under current variation. The experiment was conducted using a constant-current (CC) power supply with a voltage compliance of 37 V. Seven current levels from 0.20 A to 0.50 A were tested for approximately 7200 s, with three repetitions performed at each current level. The measurement system recorded the actual forward voltage, measured current, calculated electrical power, module temperature, and local ambient temperature. The thermal response was analyzed using the temperature difference between the module and local ambient, while the late-time thermal response was represented by the average temperature rise during the last 30 minutes of each test. The results show that increasing current increased the calculated electrical power from approximately 6.68 W to 18.00 W and increased the late-time temperature rise from 13.39 °C to 45.27 °C. A linear empirical model between electrical power and late-time temperature rise produced with . These results indicate a clear electrical-thermal relationship in the tested module, although not all current levels reached full steady-state within the test duration. Therefore, the findings are interpreted as transient and late-time thermal characteristics rather than universal steady-state behavior